Unity of heaven and humanity: Mediating role of the relational-interdependent self in the relationship between Confucian values and holistic thinking - Wang, Zhen-Dong; Wang, Yi-Meng; Guo, Huan; Zhang, Qian (Frontiers in Psychology, 2022)
As the primary value system in Chinese culture for almost 2,000 years, Confucianism has profoundly influenced the mindset of Chinese people. Cultural psychology studies have highlighted that individuals with different cultural backgrounds vary in their preferences for certain personality traits, such as self-construal, and their metacognitive characteristics, such as thinking modes. Compared to Western cultures, Chinese culture shows a preference for the interdependent self and holistic thinking. To investigate the relationship among the relational-interdependent self, holistic thinking, and traditional Chinese values (which are represented by Confucian values), we surveyed 327 Chinese adults using the Confucian Traditional Values Survey, Holistic Thinking Scale, and Relational-Interdependent Self-Construal Scale. The results showed that Confucian values positively influence both holistic thinking and the relational-interdependent self, the latter of which partially mediates the positive relationship between Confucian values and holistic thinking. The present study deepens the understanding of the psychological features of Chinese culture.